Religious and Moral Ideal in Modern Hagiographic Texts: Linguistic Characteristics - E. G. Dmitrieva (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The author considers the hagiographic texts related to the modern period of the Russian hagiography development. The source of the language material was the hagiographies of new martyrs Nikolay Popov and Iakov Gorokhov. The analysis of scientific literature on the research topic is carried out. The article deals with the controversial issues related to the identification of conceptual content and correlation of the terms ideal , moral ideal , religious and moral ideal , as well as hagiography , biography , materials for biography . The author focuses on the semantics and functioning of the vocabulary of emotions in these texts. The constant features of the use of emotive lexemes observed in the considered hagiographic texts of studied and also earlier periods (ancient Russian, old Russian, Synodal) and peculiar to the Russian hagiographic tradition as a whole are established: 1) the significance of the qualitative characteristics of emotional experience (positive / negative / neutral), 2) the presence of particularly frequent lexemes that determine the general emotional background of hagiographic text, 3) the relevance of the high intensity of emotional experience, 4) the implementation of the characterological function by emotive lexemes. The features of realization of linguistic means for creation of the image of the ascetic as a religious and moral ideal, peculiar to modern hagiographic texts and allowing to speak about their variation in accordance with the author’s intention, are revealed.